Assay Methods and Standard Preparations for Plasmin, Plasminogen and Urokinase in Purified Systems, 1967-1968 - Johnson, A. J; Kline, D. L; Alkjaersig, Norma (Thrombosis and Haemostasis, 1969)
To facilitate communication between investigators, the Committee on Thrombolytic Agents of the National Heart Institute suggests standardized reagents and assay methods for the measurement of standard preparations of plasmin, plasminogen, and urokinase with use of casein, fibrin and synthetic esters as substrates.